Decolonizing The "New Being": Rereading Tillich for the Marginalized Subject via Transformative Justice. - Bowman, Hannah (Journal of Feminist Studies in Religion (Indiana University Press))
This article proposes a decolonial feminist critique of Paul Tillich's concept of the "New Being," a new reality that overcomes existential alienation. In line with new understandings of subjectivity and subject formation that derive from postcolonial theorists including Homi Bhabha and decolonial feminist scholars Gloria Anzaldúa and María Lugones, this article proposes the individual subject as "split" or a site of multiplicity, constituted by interpersonal relationships and intersecting systems of oppression, and seeks a concept of New Being sufficient to this view of the subject. It offers a critical reconstruction of the New Being as an emergent phenomenon of resistance to self-estrangement and material oppression grounded in the particulars of marginalized/colonized identities, and draws on practices and examples from the transformative justice (TJ) movement to find New Being arising from concrete acts of justice making and resistance.